2020
DOI: 10.1089/jamp.2019.1554
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the Aerogen Mesh Nebulizer for Dried Aerosol Exposures Using the PreciseInhale Platform

Abstract: Background: Many substances used in inhalation research are water soluble and can be administered as nebulized solutions. Typical examples are therapeutic, small-molecular agents, or macromolecules. Another category is a number of water-soluble agents used for airway diagnostics or disease modeling. Mesh nebulizers have facilitated well-controlled liquid aerosol exposures. Meanwhile, a benchtop inhalation platform, Pre-ciseInhale, was developed for providing small-scale, well-controlled aerosol exposures in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…One might hypothesize that an evaporation process took place causing bacteria to be destroyed. However, for the Aeroneb® lab nebulizer used in this study, it has been observed, that smaller droplet sizes, below 2.5 µm, through evaporation were only achieved by varying experimental conditions extensively, such as by heating of the aerosol 43 46 . We chose the Aeroneb® lab nebulizer, because it is a well-characterized and specified system.…”
Section: Discussionmentioning
confidence: 73%
“…One might hypothesize that an evaporation process took place causing bacteria to be destroyed. However, for the Aeroneb® lab nebulizer used in this study, it has been observed, that smaller droplet sizes, below 2.5 µm, through evaporation were only achieved by varying experimental conditions extensively, such as by heating of the aerosol 43 46 . We chose the Aeroneb® lab nebulizer, because it is a well-characterized and specified system.…”
Section: Discussionmentioning
confidence: 73%
“…Seeking to maximize the exposure of HH-120 to SARS-CoV-2 viruses to improve its bioavailability, we evaluated whether HH-120 could be administrated via inhalation, which should support direct delivery of HH-120 (with a MW of ~1000 KDa) to the entire respiratory tract from the nose to lung, thus efficiently targeting the SARS-CoV-2 virus locally at the main infection sites. We choose a mesh vibrating nebulizer instrument (Aerogen Solo) that employs a mini pump to produce fine particles with geometric diameter range between 1–5 μm 42 (i.e., ideally sized particles for deep lung deposition 43 ). To evaluate the influence of nebulization on the physicochemical properties and neutralization activity of HH-120, HH-120 aerosols produced by the Aerogen Solo instrument were collected and analyzed: HH-120 exhibited the same SEC-HPLC peak profiles before and after nebulization, without notable aggregation or degradation, and the HH-120 main peak maintained at a high percentage level after nebulization (98.78%) as compared to that before nebulization (99.13%) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Seeking to maximize the exposure of HH-120 to SARS-CoV-2 viruses to improve its bioavailability, we evaluated whether HH-120 could be administrated via inhalation, which should support direct delivery of HH-120 (with a MW of ~ 1000KDa) to the entire respiratory tract from the nose to lung, thus e ciently targeting the SARS-CoV-2 virus locally at the main infection sites. We choose a mesh vibrating nebulizer instrument (Aerogen Solo) that employs a mini pump to produce ne particles with geometric diameter range between 1-5 µm 39 (i.e., ideally sized particles for deep lung deposition 40 ). To evaluate the in uence of nebulization on the physicochemical properties and neutralization activity of HH-120, HH-120 aerosols produced by the Aerogen Solo instrument were collected and analyzed: HH-120 exhibited the same SEC-HPLC peak pro les before and after nebulization, without notable aggregation or degradation.…”
Section: Hh-120 Can Be Effectively Nebulized Using a Mesh Vibrating N...mentioning
confidence: 99%